Developing a Mathematical Model to Predict the Behavior of a Supersonic Superheated Steam Flow inside a Laval Nozzle - H. Rezaei; S. Ovaysi; M. Rahimi (Iranian Journal of Chemical Engineering)
The objective of the investigation was to mathematically correlate the behavior of a supersonic superheated steam flow inside a Laval nozzle, against the decision parameters. The decision parameters are the inlet temperature ranging from 374.3 K to 504.3 K and the inlet pressure from 40050.14 Pa to 133375.7 Pa. Indeed, the outlet temperature, outlet pressure as well as the Mach number are mathematically correlated against the decision parameters. The numerical approach based on the Computational Fluid Dynamics (CFD) is selected to study the behavior of the supersonic superheated steam flow inside the nozzle. By examining the different temperature and pressure conditions of the inlet fluid, it was found that the closest distance from the starting point of condensation to the throat is at the highest pressure and lowest temperature. Conversely, the farthest distance from the starting point of condensation to the throat is at the lowest pressure and highest temperature. In addition, three mathematical correlations were developed. Due to the high accuracy of the mathematical correlations, the efficiency of the predictor models in predicting the outputs was proved.